PERLINDUNGAN DEMOKRASI DAN KEMERDEKAAN MAHKAMAH KONSTITUSI - Fitra Mulyawan; Kiki Yulinda; Dora Tiara (Ensiklopedia of Journal, 2023)
Democracy as a constitutional concept when used as a state ideology has many meanings and names, this is due to the many implementations of democratic values which seem to be the obsession of the world community. In our constitutional system, some basic values of constitutional democracy can no longer be questioned, because the amendments to the Constitution are contained in Article 1 paragraph (3), which states that Indonesia is a constitutional state and not based on mere power and uses a constitutional system. The existence of the Constitutional Court as one of the state institutions that exercises judicial power is a power that is independent from all kinds of extra-judicial influences and is responsible to the people through the administration of the Constitutional Court based on the principles of good and clean governance through and its decisions in accordance with the constitution, the will of the people and democratic ideals.Keywords: Democracy, Independence, Constitutional Court